The Effect of Management Information Systems and Business Assistant Mentoring on Performance through Cooperative Governance - Dylan Winalda; Sulaeman Rahman Nidar; Sutisna (Economic and Business Horizon, 2026)
The establishment of the Merah Putih Village/Sub-District Cooperative aims to strengthen local economic development through improved governance and sustainable cooperative performance. This study examines the effects of the management information system and business assistant mentoring on cooperative performance, with cooperative governance as a mediating variable. A quantitative explanatory approach was employed using survey data collected from 150 cooperative administrators and members in North Sumatra Province. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that management information systems and business assistant mentoring have positive and significant effects on cooperative governance and cooperative performance. Business assistant mentoring demonstrates the strongest influence on cooperative governance, while cooperative governance significantly enhances cooperative performance and mediates the relationships between management information systems, business assistant mentoring, and performance. These findings indicate that digital systems and managerial mentoring generate greater organizational benefits when integrated with effective governance practices. This study contributes to the cooperative management literature by integrating digital transformation, managerial capacity development, and governance into a unified analytical framework. It provides practical recommendations for policymakers to strengthen cooperative sustainability through coordinated digitalization, continuous mentoring, and governance improvement.